Keterampilan 4C dalam Pembelajaran Abad 21 di Sekolah Dasar - Fujiwaty; Eka Sustri Harida (AL-IBROH: Jurnal Ilmu Pendidikan dan Keguruan, 2025)
This study aims to examine in depth and analyze the importance of implementing 4C skills in elementary school learning, as well as to describe teachers’ strategies in fostering and developing these skills among students. This is related to the advancement of science and technology in the 21st century, which demands that the education sector produce human resources with critical thinking, creative, communicative, and collaborative abilities. These four competencies are known as the 4C skills (Critical Thinking, Creativity, Communication, and Collaboration). This study employs a literature review (library research) method by collecting several articles from Scopus, Web of Science, Google Scholar, and other academic journal websites using specific keywords such as 4C Skills, 21st-Century Learning, Elementary School, Critical Thinking, Creativity, Communication, and Collaboration. The results of the review indicate that the implementation of 4C skills in elementary schools can enhance higher-order thinking skills, foster learner autonomy, and strengthen students’ character to prepare them for global challenges. Teachers play a crucial role as facilitators in creating active, innovative, and collaborative learning environments through the application of various instructional models, such as Project-Based Learning (PjBL), Contextual Teaching and Learning (CTL), and Team Games Tournament (TGT).